Resolução CSMPF nº 82, de 19 de setembro de 2005 - Antonio Fernando Barros e Silva de Souza; Roberto Monteiro Gurgel Santos; Delza Curvello Rocha; Ela Wiecko Volmer de Castilho; Helenita Amelia Caiado de Acioli; Moacir Morais Filho; Maria Eliane Menezes de Farias; Maria Cateana Cintra Santos; Alcides Martins; Deborah Macedo Duprat de Britto Pereira (DJ, Brasília, DF, p. 695, 29 set. 2005., 2005)
Altera o art. 1º da Resolução CSMPF nº 32, de 9 de dezembro de 1997.